2017
DOI: 10.1007/s12098-017-2386-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Characterization of Prader-Willi Syndrome

Abstract: Clinical suspicion is vital for early detection of PWS. Confirmation of the diagnosis requires complex multi-tier molecular genetic testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Prader-Willi syndrome (PWS) is a complex, multisystem neurodevelopmental disorder that occurs with a frequency of approximately 1/10,000 to 1/30,000 [1] . PWS results from the loss of expression of paternally derived genes by a variety of mechanisms, which include paternally inherited deletions (70-75%), maternal uniparental disomy (20-30%), and imprinting defects (2-5%) [2,3]. DNA methylation analysis will correctly diagnose more than 99% of cases, and is the most sensitive genetic test available [1][2][3][4].…”
Section: Prader-willi Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Prader-Willi syndrome (PWS) is a complex, multisystem neurodevelopmental disorder that occurs with a frequency of approximately 1/10,000 to 1/30,000 [1] . PWS results from the loss of expression of paternally derived genes by a variety of mechanisms, which include paternally inherited deletions (70-75%), maternal uniparental disomy (20-30%), and imprinting defects (2-5%) [2,3]. DNA methylation analysis will correctly diagnose more than 99% of cases, and is the most sensitive genetic test available [1][2][3][4].…”
Section: Prader-willi Syndromementioning
confidence: 99%
“…PWS results from the loss of expression of paternally derived genes by a variety of mechanisms, which include paternally inherited deletions (70-75%), maternal uniparental disomy (20-30%), and imprinting defects (2-5%) [2,3]. DNA methylation analysis will correctly diagnose more than 99% of cases, and is the most sensitive genetic test available [1][2][3][4]. The genetic anomalies lead to a distinctive phenotype that includes central hypotonia, cognitive delay, developmental disabilities, behavioral problems, obesity, growth hormone deficiency, hypogonadism, and lifethreatening hyperphagia [1].…”
Section: Prader-willi Syndromementioning
confidence: 99%
“…Prader-Willi syndrome (PWS) is a neurogenetic multisystem disorder characterized by short stature, hypogonadism, dysmorphic features, hyperphagia, mental retardation, and behavior problems, including temper tantrums, stubbornness, obsessive-compulsive behaviors, and skin picking. 1 Bhargava et al 2 reported 3 patients with PWS in whom an extension of this skin picking behavior to rectal picking resulted in significant lower gastrointestinal bleeding and anorectal disease. Occasionally, the lesion may exhibit a tumor-like elevation, 3 similar to that observed in this patient, which is thought to result from the physical and mechanical irritation caused by repetitive scratching of the rectum with fingers.…”
Section: Answer To: Image 5 (Page 2039): Rectal Ulcer and Inflammatormentioning
confidence: 99%
“…Mild intellectual impairment, hypogonadism and sleep apnea have been also associated with PWS. Patients often exhibit characteristic facial features such as almond-shaped up-slanted palpebral fissures, thin upper lip and small mouth with down-turned corners [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hypopigmentation of the iris and choroid, diabetic retinopathy, cataract, congenital ocular fibrosis syndrome and congenital ectropion uvea have also been reported [ 3 ]. Table 1 summarizes intraocular findings reported by previous publications in the context of PWS [ 2 – 29 ]. Herein, we report novel ocular findings in a case of PWS using multimodal imaging.…”
Section: Introductionmentioning
confidence: 99%